Two-level factorial design for the extraction of phenolics and flavonoids from chromolaena odorata leaves - Alara, Oluwaseun Ruth; Nour, A. H.; Siti Kholijah, Abdul Mudalip; Olalere, Olusegun Abayomi (2018)
Chromolaena odorata (Bitter bush) belongs to the family Asteraceae. It is used as a source of medicine especially in Asia and West Africa countries [1]. Phenolic compounds are mostly distributed group of phytochemicals that possess a wide range of physiological activities like antiinflammatory, anti-cancer, vasodilatory effects, antioxidant, and among others [2]. Several phenolic compounds have been extracted and isolated from this plant, including vanillic acid, pcoumaric, protocatechuic, quercetin, luteolin, kaempferol, and among others [3]. The effects of microwave-assisted extraction (MAE) variables on the recovery yields of total phenolic content (TPC) and total flavonoid content (TFC) from Chromolaena odorata leaves were investigated using single factor experiment and two-level factorial design. The examined MAE variables were irradiation time, A (1-5 min), microwave power level, B (400-800 W), temperature, C (60-80 °C), solvent-feed ratio, D (8-14 ml/g) and ethanol concentration, E (20-60%). The obtained results showed that irradiation time (3.90 %), microwave power level (14.93 %) and ethanol concentration (17.21 %) significantly contributed to the recoveries of TPC and TFC from Chromolaena odorata leaves (Fig. 1). This implies that irradiation time, microwave power and ethanol concentration were significant (p < 0.05) in obtaining higher recoveries. Thus, the significant variables will be considered for the optimization process